In Vitro and in Vivo Selection of Potentially Probiotic Lactobacilli From Nocellara del Belice Table Olives - Guantario, Barbara; Zinno, Paola; Schifano, Emily; Roselli, Marianna; Perozzi, Giuditta; Palleschi, Claudio; Uccelletti, Daniela; Devirgiliis, Chiara (Frontiers in Microbiology, 2018)
Table olives are increasingly recognised as a vehicle as well as a source of probiotic bacteria, especially those fermented with traditional procedures based on the activity of indigenous microbial consortia, originating from local environments. In the present study, we report characterisation at the species level of 49 Lactic Acid Bacteria strains deriving from Nocellara del Belice table olives fermented with the Spanish or Castelvetrano methods, recently isolated in our previous work. Ribosomal 16S DNA analysis allowed identification of 4 Enterococcus gallinarum, 3 E. casseliflavus, 14 Leuconostoc mesenteroides, 19 Lactobacillus pentosus, 7 L. coryniformis and 2 L. oligofermentans. The L. pentosus and L. coryniformis strains were subjected to further screening to evaluate their probiotic potential, using a combination of in vitro and in vivo approaches. The majority of them showed high survival rates under in vitro simulated gastro-intestinal conditions, and positive antimicrobial activity against Salmonella enterica serovar Typhimurium, Listeria monocytogenes and enterotoxigenic Escherichia coli (ETEC) pathogens. Evaluation of antibiotic resistance to ampicillin, tetracycline, chloramphenicol or erythromycin was also performed for all selected strains. Three L. coryniformis strains were selected as very good performers in the initial in vitro testing screens, they were antibiotic susceptible, as well as capable of inhibiting pathogen growth in vitro. Parallel screening employing the simplified model organism Caenorhabditis elegans, fed the Lactobacillus strains as a food source, revealed that one L. pentosus and one L. coryniformis strains significantly induced prolongevity effects and protection from pathogen-mediated infection. Moreover, both strains displayed adhesion to human intestinal epithelial Caco-2 cells and were able to outcompete foodborne pathogens for cell adhesion. Overall, these results are suggestive of beneficial features for novel LAB strains, which renders them promising candidates as starters for the manufacturing of fermented table olives with probiotic added value.